Using the natural environment in Polish plans for the future war in the thirties of the 20th century - Wojtaszak, Andrzej (Armia kontra natura, 2020)
In the last decade preceding the outbreak of World War II, the war threat of Poland was perceived by the highest political and military authorities. During the reign of Józef Piłsudski the question was asked: who was the war with? This question asked to the military and political decision makers confirmed three possibilities of the outbreak of the conflict: with Russia, with Germany and with Russia and Germany. The analyzes carried out took into account the use of the natural environment as an important element in the preparation of variants of strategic plans for the future war. Each of the plans took into account the complexity of the defense situation of the state (special, long line of borders, natural obstacles and lack thereof). The Polish military alliances were counted on. The Polish defensive war of 1939 turned out to be a conflict with two aggressors (the Third Reich and the USSR), and with the passivity of our Allies, the chances of victory were only hypothetical. The natural environment may help in the implementation of military action plans, but it does not replace the lack of military capabilities of the army.